Contemporary Neuroscience Core Curriculum for Medical Schools. (5th October 2021) - Gelb, Douglas J.; Kraakevik, Jeff; Safdieh, Joseph E.; Agarwal, Sachin; Odia, Yazmin; Govindarajan, Raghav; Quick, Adam; Soni, Madhu; Bickel, Jennifer; Gamaldo, Charlene; Hannon, Peter; Hatch, Hayden A.M.; et al.
Abstract : Medical students need to understand core neuroscience principles as a foundation for their required clinical experiences in neurology. In fact, they need a solid neuroscience foundation for their clinical experiences in all other medical disciplines also because the nervous system plays such a critical role in the function of every organ system. Because of the rapid pace of neuroscience discoveries, it is unrealistic to expect students to master the entire field. It is also unnecessary, as students can expect to have ready access to electronic reference sources no matter where they practice. In the preclerkship phase of medical school, the focus should be on providing students with the foundational knowledge to use those resources effectively and interpret them correctly. This article describes an organizational framework for teaching the essential neuroscience background needed by all physicians. This is particularly germane at a time when many medical schools are reassessing traditional practices and instituting curricular changes such as competency-based approaches, earlier clinical immersion, and increased emphasis on active learning. This article reviews factors that should be considered when developing the preclerkship neuroscience curriculum, including goals and objectives for the curriculum, the general topics to include, teaching and assessment methodology, who should direct the course, and the areas of expertise of faculty who might be enlisted as teachers or content experts. These guidelines were developed by a work group of experienced educators appointed by the Undergraduate Education Subcommittee (UES) of the American Academy of Neurology (AAN). They were then successively reviewed, edited, and approved by the entire UES, the AAN Education Committee, and the AAN Board of Directors.